SWINDLERT©: development of augmented reality game-based interactivity for enhancing cybercrime awareness / Sakinah Ali Pitchay ... [et al.] - Ali Pitchay, Sakinah; Azni, A.H; Ridzuan, Farida; Mohd Alwi, Najwa Hayaati; Imran, Muhammad Syahmi (UiTM Cawangan Perlis, 2025)
As digital technologies advance, cybercrime has become a primary global concern, posing threats to individuals and organisations. Despite widespread Internet use, public awareness of cybercrime risks is still limited, emphasising the need for educational initiatives. The lack of engaging educational tools for cybercrime awareness is due to outdated, overly technical approaches that fail to captivate modern audiences. Limited investment and collaboration between cybersecurity experts and educational designers result in resources that are not as appealing or user-friendly as they could be. Therefore, this paper introduces SWINDLERT, an augmented reality (AR) game-based tool in a three-dimensional (3D) environment designed to enhance cybercrime awareness and educate users on early prevention. It addresses three key issues: (i) carelessness in sharing credentials, (ii) lack of cybercrime prevention literacy, and (iii) low student engagement in traditional lecture-based education. It has three main objectives: (i) to identify types of cybersecurity crime prevention, (ii) to develop an edutainment AR mobile game with 3D images, and (iii) to evaluate functionality and security. Using Agile methodology, we conduct user requirements through surveys and test the application at SK Teluk Ketapang, Terengganu, and Universiti Sains Islam Malaysia. 98% agree that SWINDLERT has effectively embedded good gamification elements such as levels, scores and timers. Users benefit from password complexity, email verification, and the ability to retrieve their progress on multiple devices. The game features three levels: beginner, intermediate, and hard. This approach blends immersive technology by integrating an AR quiz-based 3D snake and ladder board gamification to transform education, making learning engaging and enjoyable.